Phospholipase A2 myotoxins from Bothrops snake venoms - Gutiérrez, José María (1995)
The genus Bothrops is distributed over all Latin America, From Mexico to Argentina, and comprises nearly 31 species of snake. In most of these countries, Bothrops spp. cause the majority of snake bit envenomations, which are characterized by conspicuous local tissue damage including hemorrhage, edema and myonecrosis. In recent years, research efforts to understand the Bothrops venon-induced myonecrosis have resulted in the isolation and characterization of a group of toxic proteins which are mainly responsible for this effect.